A multi-institutional analysis of Textbook Outcomes among patients undergoing cytoreductive surgery for peritoneal surface malignancies. (June 2021) - Wiseman, Jason T.; Abdel-Misih, Sherif; Beal, Eliza W.; Zaidi, Mohammad Y.; Staley, Charles A.; Grotz, Travis; Leiting, Jennifer; Fournier, Keith; Lee, Andrew J.; Dineen, Sean; Powers, Benjamin; Veerapong, Jula; et al.
Abstract: Background: While recent studies have introduced the composite measure of a textbook outcome (TO) for measuring postoperative outcomes, the incidence of a TO has not been characterized among patients undergoing cytoreductive surgery (CRS) for peritoneal surface malignancies (PSM). Study design: All patients who underwent CRS ± hyperthermic intraperitoneal chemotherapy (HIPEC) between 1999 and 2017 from 12 institutions were included. A TO was defined as the absence of any of the following criteria: completeness of cytoreduction >1, reoperation within 90-days, readmission within 90-days, mortality within 90-days, any grade ≥2 complication, hospital stay >75th percentile, and non-home discharge. Results: Among 1904 patients who underwent CRS, only 30.9% achieved a TO while 69.1% failed to achieve a TO most commonly because of postoperative complications. On multivariable analysis, factors associated with achieving a TO were age <65 years (OR: 1.5), albumin ≥3.5 g/dl (OR: 5.7), receipt of HIPEC (OR: 4.5), PCI ≤14 (OR: 2.2), intravenous fluid volume ≤10, 000 ml (OR: 2.1), blood loss ≤1000 ml (OR: 4.2) and operative time <7 h (OR: 1.9); while receipt of neoadjuvant therapy (OR: 0.7) and liver resection (OR: 0.4) were associated with not achieving a TO (all p < 0.05). TO was associated with improved overall survival (median 159 months vs 56 months, p < 0.01) even after controlling for confounders on Cox regression (hazard ratio: 2.5, p < 0.01). Conclusion: Among patients undergoing CRS ± HIPEC for PSM, failure to achieve a TO is common and independently associated with worse overall survival. Highlights: A textbook outcome (TO) was achieved in 30.9% of patients undergoing CRS ± HIPEC for PSM. Failure to achieve a TO was most commonly because of postoperative complications. Not achieving a TO was associated with neoadjuvant therapy and liver resection. Achieving a TO was associated with improved overall survival. Abstract : Among patients undergoing cytoreductive surgery ± heated intraperitoneal chemotherapy, failure to achieve a "textbook outcome" is common and associated with worse overall survival.